Liability of Airlines That Unilaterally Cancel Flights in Indonesia - Rahmawati Dewi, Stepani; Aulia, Muhammad Fikri; Gunawan, Moh Sigit; Maulida, Irma (Jurnal Legisci, 2025)
Background, Aviation is one of the significant forms of business deregulation in Indonesia. The existence of aircraft makes it easy for passengers to move between regions quickly and efficiently for various purposes. The commercial air transportation sector is growing rapidly, as seen by the increasing number of airlines providing flight services and the rising public interest in using these services. However, in reality, many consumer rights have not been fully fulfilled by airlines, especially in the case of flight delays. For this reason, strict legal regulations are needed to regulate airlines' responsibilities to protect consumer rights. In its implementation, it turns out that passengers submit many complaints to the airline due to various problems. Aim, Clear and firm legal regulations are needed to regulate airlines' responsibilities to protect passengers' rights. This research focuses on two main issues, namely how the airline's liability to passengers is related to flight schedule delays and how to claim compensation for airline passengers related to flight schedule delays. Methods, This study uses a normative juridical approach by analysing laws and regulations related to legal protection for consumers. The data obtained was analysed qualitatively to understand the issue more deeply. Results, The study results show that the Regulation of the Minister of Transportation Number 89 of 2015 expressly regulates the rights of consumers affected by flight delays and stipulates the obligations of airlines to aggrieved passengers. Conclusions, The legislation was made to ensure that passengers get safety and security in running flights, as well as passengers, are more independent and know the importance of the issuance of the law. Implication, Furthermore, the regulation can be used as a foothold for passengers' legal protection against problems.